Hubungan Jenis Makanan dan Pengetahuan Gizi dengan Kejadian Kekurangan Energi Kronis pada Ibu Hamil - Bonita, Ika Amalina; Rifqiyah, Najihatur; Rafika, Muhana; Nursihhah, Meliana (Media Gizi Ilmiah Indonesia, 2025)
Pregnant women with chronic energy deficiency status tend to give birth to low birth weight babies and face a greater risk of death. Chronic energy deficiency was a condition where the mother experiences a lack of food intake that last long (chronic) causing health problems. Incidence of chronic energy deficiency in pregnant women was characterized by an upper arm circumference of ≤ 23.5 cm. Food consumption with balanced food types and good of nutrition knowledge could decrease incidence of chronic energy deficiency in pregnant women. This research aimed to determine relationship of food types and nutrition knowledge with incidence of chronic energy deficiency in pregnant women. This research used a observasional analytic with a case-control design. This research was conducted in July-Agustus 2023 at Ciwaringin Public Health Center, Cirebon. The sampling technique used slovin with a total sample of 74 people, consisting of 37 cases and 37 controls. The sample of case group used purposive sampling and control group used sample random sampling. Food types data used a food frequency questionnaire (FFQ) and nutrition knowledge used nutrition knowledge questionnaire. Nutritional status data measured using a LILA tape. Based on chi-square test found that food types (OR= 3.5 (95%CI: 1-12.2) had a significant related and had chance to decrease of chronic energy deficiency in pregnant women (p<0.05), while nutrition knowledge no significant related (p>0.05). Food types had chance to decrease of chronic energy deficiency in pregnant women, while nutrition knowledge no significant related.